2022
DOI: 10.54783/influencejournal.v4i1.21
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Audit Tenure and Size of Public Accountant Firm on Audit Report Lag with Auditor Industry Specialization as Moderating Variable

Abstract: Relevance is one of the qualitative qualities of financial statements. If financial statements are submitted on time, they can be considered relevant. Audit report lag is closely related to timely report submission. It can increase the efficiency and quality of financial reports and enable users to rely on financial statement information when making judgments. The amount of enterprises still filing financial reports late demonstrates that punctuality remains a serious hurdle for Indonesian businesses. In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…Additionally, market pressure compels corporations to release financial reports on schedule. The findings of this study do not support the findings of (Shofiyah & Wilujeng Suryani, 2020), (Sudradjat et al, 2022), (Diana & Hidayat, 2022) which contend that the size of the company does not always significantly affect the delay in the release of audit reports. The findings of this study, however, are consistent with those of (Satyawan & ahmmi, 2020), (Machmuddah et al, 2020), who found that the magnitude of the company size always indicate how short an organization's audit report lag will be.…”
Section: Results Of Hypothesis Testingcontrasting
confidence: 99%
See 4 more Smart Citations
“…Additionally, market pressure compels corporations to release financial reports on schedule. The findings of this study do not support the findings of (Shofiyah & Wilujeng Suryani, 2020), (Sudradjat et al, 2022), (Diana & Hidayat, 2022) which contend that the size of the company does not always significantly affect the delay in the release of audit reports. The findings of this study, however, are consistent with those of (Satyawan & ahmmi, 2020), (Machmuddah et al, 2020), who found that the magnitude of the company size always indicate how short an organization's audit report lag will be.…”
Section: Results Of Hypothesis Testingcontrasting
confidence: 99%
“…It further explains that an auditor who has a long assignment with a client company will encourage the creation of business knowledge so as to enable the auditor to design an effective audit program and high quality audited financial reports. (Diana & Hidayat, 2022) stated that when the auditor and client establish a cooperative relationship for a relatively long period of time, it will provide benefits for both the client and the auditor. The length of the audit engagement period with the client can assist the auditor in obtaining due diligence, accuracy and audit expertise.…”
Section: Hypothesis Development the Effect Of Audit Tenure On Audit R...mentioning
confidence: 99%
See 3 more Smart Citations